Isolation and Antibacterial Activity Test of Mangrove Rhizosphere Bacteria Against Escherichia coli and Staphylococcus aureus - Asriatno, Okto; Dewinta Nur Alvionita; Muhammad Syarief; Dwirariska Aprilianasari Syamsuardi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The global rise in multidrug-resistant pathogens necessitates the exploration of unique ecological niches, such as the mangrove rhizosphere, as promising reservoirs for novel antibacterial agents. In this study, we aimed to isolate and characterize bacteria from the rhizosphere of Rhizophora sp. in the mangrove forest of Bypass Kendari, Southeast Sulawesi, and to evaluate their antibacterial activity against Escherichia coli and Staphylococcus aureus. Isolation was performed using the spread plate method on three different media: Nutrient Agar (NA), Zobell Marine Agar (ZMA), and International Streptomyces Project 2 (ISP2). A total of seven bacterial isolates were obtained (NA.1, ZMA.1, ZMA.2, ZMA.x, ISP2.1, ISP2.2, and ISP2.x), exhibiting diverse morphological characteristics ranging from mucoid to smooth colonies. Antibacterial screening using a modified Kirby-Bauer disc diffusion method revealed that only one isolate, ZMA.1, possessed broad-spectrum antagonistic activity, effectively inhibiting both the Escherichia coli and Staphylococcus aureus. Further microscopic identification via Gram staining characterized isolate ZMA.1 as a Gram-negative and rod-shaped bacteria, appearing in monobacillus and diplobacillus arrangements. These findings underscore the potential of Gram-negative bacteria from the mangrove rhizosphere as a promising source of new antibacterial candidates to combat multidrug-resistant pathogens.